The investments stimulation in agricultural and rural infrastructure - Dobroţeanu, Camelia (Economics of Agriculture, 2010)
The paper analyzes the investments evolution in Romanian agriculture between 2006 -2009 and their economic efficiency, and the tendency of the promoted policies by international organizations in the field in the next period. There are presented also national and community programs that promote measures to stimulate investment process in the countryside. In the actual global and national macroeconomic context it is necessary to adapt the existing policies and mechanisms to stimulate investment in agriculture to rural needs and realities.